THE IMPACT OF CONFLICTS IN SUEZ CANAL AND RED SEA ON WORLD CONTAINER SHIPPING FLEET AND SERVICES - Akimova, Olga (Sworld-Us Conference proceedings, 2025)
The article analyzes the consequences of changes in shipping routes that arose because of attacks on vessels in the Red Sea. These consequences have negative and positive impacts on ship carrying capacity, deployment patterns, order books, construction, d